Dal «vento inaridito delle pietre» alle «beate rose». Franco Fortini e l’equivoco della storia - Agliozzo, Andrea (L’ospite ingrato, 2025)
This paper examines the relationship between tradition, memory and history in Franco Fortini’s poetry, focusing on the formal strategies that convey a critique of historical linearity and enable the dialectical and critical reuse of inherited forms. The analysis of two texts – Sestina a Firenze and La poesia delle rose – shows how the tension between necessity and contingency, continuity and rupture, yields a vision of history – and of poetry – that is non-univocal, marked by discontinuities and conflicts, and reflects a situated intellectual stance that can be summarised in the formula «with history, against history». The aim is to assess the contemporary relevance of Fortini’s critical tools, elaborated through forms, within the framework of a dialectic between distance and resynchronisation that makes it possible to question his reception in the present.